2014
DOI: 10.1007/s00253-014-5927-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antimicrobial peptide L-K6, a temporin-1CEb analog on oral pathogen growth, Streptococcus mutans biofilm formation, and anti-inflammatory activity

Abstract: Dental caries and periodontitis are common bacterial mouth infections. As a potentially attractive substitute for conventional antibiotics, antimicrobial peptides have been widely tested and used for controlling bacterial infections. In this study, we tested the efficacy of the peptides from the skin secretions of Rana chensinensis for killing several major cariogenic and periodontic pathogens as well as Candida albicans. L-K6, a temporin-1CEb analog, exhibited high antimicrobial activity against the tested or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…According to structure/activity relationship studies by Giangaspero et al [36], we concluded that this poor efficacy may be related to that KSL does not adopt the optimal structure of cationic, amphipathic α-helical AMPs. Similarly, we analysed the sequence and structure of a 13-residue AMP L-K6, whose hydrophilic sector was also not clearly separate from the hydrophobic sector [16]. Thus, our strategy is to design and synthesize de novo a series of cationic AMPs that would be shorter, and adopt optimal amphipathic α-helical structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to structure/activity relationship studies by Giangaspero et al [36], we concluded that this poor efficacy may be related to that KSL does not adopt the optimal structure of cationic, amphipathic α-helical AMPs. Similarly, we analysed the sequence and structure of a 13-residue AMP L-K6, whose hydrophilic sector was also not clearly separate from the hydrophobic sector [16]. Thus, our strategy is to design and synthesize de novo a series of cationic AMPs that would be shorter, and adopt optimal amphipathic α-helical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Designed through integration of existing design strategies, GH12 owns the optimal net positive charge, content of hydrophobic residues and relative amphipathicity, adopts >80% the α-helical composition and shows superior antimicrobial activity against S. mutans with MIC and MBC of 8 mg/L [21]. Notably, Shang et al [16] deduced that L-K6 exerts bactericidal rather than bacteriostatic activity against S. mutans , due to that the MBC values (12.5 μM, 19.40 mg/L) of L-K6 against S. mutans were four-fold higher than the MIC values. However, the MIC and MBC of GH12 against S. mutans were very close, suggesting that GH12 may have other potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, without targeting and reducing dental plaque, fluoride products are unable to completely inhibit dental caries (Fejerskov 2004). Natural products and derivatives, such as green tea catechins (Hirasawa et al 2006), cranberry constituents , Galla chinensis (Xie et al 2008), citrus lemon oil (Liu et al 2013), mushroom extracts (Yano et al 2010), and several bioactive macromolecules (Shang et al 2014;Lee and Park 2015), have been reported to be effective against the growth and adherence of S. mutans. In addition, small molecules, such as tt-farnesol (Koo et al 2003), walkmycin C (Eguchi et al 2011), and anthraquinones (Coenye et al 2007), have been shown to inhibit the growth of cariogenic bacteria, and even the development of caries, but few of these compounds target S. mutans biofilms.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…3). In particular, the MsSN1 dimer showed an exceptionally high affinity for the vWF domain in terms of the predicted equilibrium dissociation constant (K d, pred (Overhage et al, 2008), the fungal peptide decapeptide KSL (Liu et al, 2011), the bovine peptide indolicidin (de la Fuente-Núñez et al, 2012) and the frog peptide L-K6 (Shang et al, 2014), have been recently identified as biofilm inhibitory compounds. In contrast, previous studies and the results reported here show that snakin peptides exposure markedly increased bacterial aggregation, adhesion and subsequent biofilm formation, suggesting that the inhibitory effect of snakin and other antimicrobial peptides occurs by a different mechanism.…”
Section: Molecular Docking Of the Complexes Between Mssn1 And The Vwfmentioning
confidence: 99%